Academic Writing in the Context of Applied Linguistics for English Language Teaching: Integrating Web 2.0 - Ortega Andrade, Dolores del Rocío (Kronos – The Language Teaching Journal, 2018)
The goal of this study was to investigate the effects of the Web 2.0 tools: Web Quest, blog, wiki and forum on EFL Academic Writing performance. 29 students majoring in Applied Linguistics to English Language at a University in Ecuador were involved. Both, quantitative and qualitative approaches were employed. Research instruments included a pre-test, a post-test; and a survey of satisfaction. Students were divided in both control and experimental groups. The control group received the teaching through a textbook; and the experimental one used the technological tools. Students’ Academic Writing performance was compared through tests. The pre-test determined the level of academic writing performance at the beginning of the experiment. The post –test determined if there were differences between the groups and differences on the experimental group scores. The findings revealed that students of the experimental group improved their scores, which suggests that the use of Web 2.0 tools can be effective and interesting for EFL Academic Writing classes. The results of the survey of satisfaction showed that most of the students had positive attitudes towards the implementation of the technological tools; they indicated that learning activities made students more engaged in the learning process and cooperative learning; and motivated.